Några tankar om nordisk barnlitteratur och dess översättning ur ett polskt perspektiv - Dymel-Trzebiatowska, Hanna (Folia Scandinavica Posnaniensia, 2016)
The article explores two aspects of translations of Nordic children’s literature, which is more and more often defined by its authors as aimed at all readerships with no respect to age (allålderslitteratur). This stance may affect the theory of translation in reference to the category of the implied reader, which will have to be reconsidered. The concept of allage literature is presented in the article as a solution to long academic discussions about the presence of an adult implied reader of children’s literature. The other perspective shows the presence of Scandinavian picturebooks on the Polish book market which have been published within the latest decade (e.g. by Svein Nyhus, Gro Dahle, Pernilla Stalfelt, Pija Lindenbaum, and Ulf Nilsson). These books are brave, taboo-breaking and translated without purifications, which refutes Elżbieta Zarych’s (2016) observations about the rules and mechanisms which are prevalent, i.e. that translators are still expected to mitigate and omit painful moments. The final part combines two aspects – the above-mentioned translations are free of adaptations, but it is difficult to assess whether the translators have taken into account the postulates of Scandinavian authors and their ambition to create all-age literature. Answers to the questions posed at the end (e.g. if the books are created for all, should they be translated for all?) might complete the translation studies with important and future oriented insights.